Penalties reworked - Conte, C (2014)
An ‘agreed damages clause’ is a contractual provision whereby the parties agree on the damages one party must pay if that party breaches a term. A valid agreed damages clause, known as a ‘liquidated damages clause’, is enforceable. An invalid agreed damages clause, known as a ‘penalty clause’, is not. The ‘penalty rule’ is the legal doctrine that discriminates between the two types of clauses. This thesis adopts a rights-based, interpretive and formalist methodology to examine the penalty rule as it has evolved, and exists today, in Anglo-Australian commercial law. The investigation proceeds in three parts. First, this thesis restates the law. It derives a principled account of the rule from the leading cases. Second, the thesis justifies the law as restated. It reveals a theory that rationally explains the penalty rule, providing good or legitimate reasons why the rule is as it is. Finally, this thesis refines the restated law in the light of its theoretical justification. It takes interpretive steps to improve the penalty rule, casting the rule in the best possible light. This thesis concludes that a penalty clause is best understood as requiring one party, upon a default, to incur a detriment that is manifestly excessive in light of the clause’s legitimate function. The refined penalty rule invalidates a penalty clause by rendering it partially unenforceable. Also, this thesis illustrates that the rule encapsulates a principle of preventing consensual civil punishment, and that corrective justice norms justify that principle. As such, the penalty rule ultimately instantiates corrective justice. Further, this thesis demonstrates that a classificatory, correctivist theory scores extremely well on several criteria for evaluating private law theories. Such a rights-based theory is highly transparent, powerfully coherent, and practically beneficial. It also displays a tight fit with the current law. In short, this thesis concludes that, viewed in the best possible light, the penalty rule is certain, elegant and (correctively) just.